Computing the PUE of data centres by leveraging workload fluctuation. (1st January 2014) - Xu, Yongmei; Deng, Yuihui; Du, Lan
Benchmarking the data centre's energy efficiency is a key step towards optimising and reducing the power consumption and the related energy costs. Power usage effectiveness (PUE) was coined by the members of American Green Grid as an index to measure the energy efficiency of data centres. Traditional approaches of calculating the PUE in data centres only consider the impact of the weighted time, but ignore the impact of the corresponding workload. These methods cannot accurately reflect the long-term energy efficiency of data centres. Since the power consumed by IT equipments and the temperature generated by the equipments normally grow with the increase of the workload intensity, an effective method employed to calculate the PUE of data centres has to consider the impacts of workload. In contrast to the traditional methods, this paper proposes an approach to compute the PUE by leveraging the workload fluctuation. Theoretical analysis and experimental evaluation demonstrate that the proposed approach can achieve a more accurate PUE than that of the traditional methods.